THE UTILIZATION STUDY OF PLACE FISH AUCTION IN VILLAGE SASAK RANAH PASISIE,SOUTH PASAMAN BARAT REGENCY SUMATERA BARAT PROVINCE - Renti Astuti; Syaifuddin Syaifuddin; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAKSasak Ranah Pasisie village is one of villages in south Pasaman Barat  Regency  owning a Place of Fish Auction ( TPI ). Sasak Ranah Pasisie TPI expected to me community consumption on marine fish locally (Sout Pasaman Barat Regerency). Sasak Ranah Pasise  Development was very well done,according to near fishing ground an suported by fisherman’s and armada’s and kualifikasi organizer education  which  enough nicely.  Beside, every day of fish landed always sellout cause the exis of  transportation so that the  marketing go out area is not annoyed. This research aimed to look at the condition and facility usage which existed in Sasak Ranah Pasisie TPI and probability for development. The adventage of this research was giving suggestion and consideration to development of TPI facility in the future. The data Analysed consisted of technical analysis . According to the research and result and tehnical count result, the facilities and it’s utilization.  Keyword : Fish Auction Place, the condition offacility, capacity